MKRN3 and KISS1R mutations in precocious and early puberty - Sara Pagani; Valeria Calcaterra; Gloria Acquafredda; Chiara Montalbano; Elena Bozzola; Pietro Ferrara; Manuela Gasparri; Alberto Villani; Mauro Bozzola (BMC, 2020)
Abstract Background Pubertal timing is known to be influenced by interactions among various genetic, nutritional, environmental and socio-economic factors, although the ultimate mechanisms underlying the increase in pulsatile GnRH secretion at puberty have yet to be fully elucidated. The aim of our research was to verify the role of KISSR1 (previously named GPR54) and MKRN3 genes on pubertal timing. Methods We analyzed the DNA sequence of these genes in 13 girls affected by central precocious puberty (CPP) who showed onset of puberty before 8 years of age, and in 6 girls affected by early puberty (EP) between 8 and 10 years of age. Results Direct sequencing of the KISS1R (GPR54) gene revealed two SNPs. One SNP is a missense variant (rs 350,132) that has been previously reported in connection to CPP in Korean girls. The other variant that we found in the GPR54 gene (rs764046557) was a missense SNP located in exon 5 at position 209 of the aminoacid. We identified this variant in only one CPP patient. Automatic sequencing of MKRN3 in all patients revealed three variants in eight subjects. In 6 out of 19 (31.5%) patients (3/13 CPP patients and 3/6 EP patients) we found the synonymous variant c.663C > T (rs2239669). Another synonymous variant (rs140467331) was found in one of our CPP patients, as well as one missense variant (rs760981395) in another CPP patient. Conclusion In conclusion, we identified sequence variations of the KISS1R and MKRN3 genes, two of the most frequent genetic causes of ICPP. Our results suggest that these variants might be inducible factors in the pathogenesis of CPP.